2017
DOI: 10.1177/2048872617711169
|View full text |Cite
|
Sign up to set email alerts
|

Intra-aortic balloon pump protects against hydrostatic pulmonary oedema during peripheral venoarterial-extracorporeal membrane oxygenation

Abstract: Associating an IABP with peripheral VA-ECMO was independently associated with a lower frequency of hydrostatic pulmonary oedema and more days off mechanical ventilation under ECMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 41 publications
0
81
0
5
Order By: Relevance
“…As ECMO increases afterload of LV and reduces coronary artery blood flow, combining with IABP could make up for the shortages of ECMO support. Previous studies showed that additional application of IABP reduced pulmonary artery occlusion pressure and hydrostatic pulmonary edema, and increased cerebral blood flow in patients with ECMO . However, it is still controversial whether combining application of IABP improves survival of patients with ECMO support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As ECMO increases afterload of LV and reduces coronary artery blood flow, combining with IABP could make up for the shortages of ECMO support. Previous studies showed that additional application of IABP reduced pulmonary artery occlusion pressure and hydrostatic pulmonary edema, and increased cerebral blood flow in patients with ECMO . However, it is still controversial whether combining application of IABP improves survival of patients with ECMO support.…”
Section: Discussionmentioning
confidence: 99%
“…An intra‐aortic balloon pump (IABP) could reduce LV afterload and increase coronary artery blood flow through inflating during diastole and deflating during systole. In addition, IABP implantation showed reduced pulmonary artery occlusion pressure and hydrostatic pulmonary edema, and increased cerebral blood flow in patients with ECMO . Combined use of IABP with ECMO is common in PCS, with a rate of 25 to 74% in various centers .…”
mentioning
confidence: 99%
“…IABP is frequently used in cardiogenic shock to improve diastolic coronary perfusion, as well as reduce left ventricular afterload and pulmonary edema. When used together with VA-ECMO it may improve coronary and cerebral perfusion, [68][69][70][71] facilitate left ventricular unloading and weaning from VA-ECMO, 72 reduce hospital mortality, 73 and reduce the risk of pulmonary edema 74 .…”
Section: Iabpmentioning
confidence: 99%
“…Brechot et al 74 conducted a retrospective single center study of 259 patients requiring VA-ECMO support, of whom 104 also received IABP support. Chest X-rays were assessed, and pulmonary edema was graded according to the Weinberg radiologic score.…”
Section: Iabpmentioning
confidence: 99%
“…La experiencia por el momento es baja, el coste con respecto a la ECMO es mayor, pueden no aportar el suficiente soporte hemodinámico en los pacientes más graves (12), y son difíciles de implementar en los programas de transporte primario. En cuanto al BIAC ya no se recomienda de forma rutinaria en el shock cardiogénico (18), aunque sí hay estudios que apoyan su uso concomitante a la ECMO VA al mejorar la hemodinámica y disminuir el riesgo de EAP (40,41). No existen estudios prospectivos exclusivamente de transporte de pacientes con shock cardiogénico.…”
Section: Criterios De Ecmo Para Traslado En El Shock Cardiogénicounclassified